CHANGES IN GLUTATHIONE PEROXIDASE ACTIVITY IN CARDIAC TISSUES OF RATS IN RESPONSE TO MECHANICAL INJURY OF THE BLOOD-OCULAR BARRIER - O. N. Gulenko; A. A. Devyatkin; P. V. Boriskin; O. N. Pavlova; V. V. Leonov; R. G. Karimova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Mechanical eye injury and damage to the blood-ocular barrier cause inflammation resulting in oxidative stress,  which, in turn, triggers myocardial ischemia, since the heart's need for oxygen exceeds its supply. A rapid decrease in the oxygen concentration in ischemic tissues causes a switch from oxidative to anaerobic metabolism, when  energy deficit initiates a chain of physiological processes. The discovery of the molecular mechanisms underlying  the manifestation of oxidative stress in the cardiac tissues will enable the development of effective therapeutic  approaches to such condition. Objective: to analyze the dynamics of glutathione peroxidase (GP) activity in cardiac tissues of rats in response to oxidative stress caused by mechanical eye injury.Materials and methods. In our experiment, we used 150 healthy white mature (8-month old) male rats weighing 190–210 g and kept under standard conditions in a vivarium. GP activity was evaluated before the experiment and then on days 1, 3, 5, 7, and 14. Nonparametric statistical analysis was used in this study. Conclusion. GP activity in cardiac tissues of rats during oxidative stress caused by mechanical eye injury was most effectively stabilized by standard treatment for mechanical eye injury plus injections of quercetin.